PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN SAINTIFIK PADA MATERI PEMANASAN GLOBAL - Diana Nur Nadiya Fitriya; Nur kuswanti; Oktaffi Arinna Manasikana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2021)
This research was conducted based on the science learning process which is stillcentered on the teacher (teacher center) and is still fixated on textbooks, so it requireslearning resources in the form of LKPD. The purpose of this study was to determine thefeasibility of student worksheets developed based on the validity of the LKPD based on thescientificoapproach. The type of research used in this researchiisdevelopmentjresearchjusing thejADDIE developmentpmodel whichjconsists of severalstagesk namely, Analysis,iDesign, Development, Implementation,iandEvaluation.oHowever, the implementation stage could not be implemented due to the covid19 pandemic. The subjects ofithis studyiconsisted of experts (material experts andvalidation experts). The expert provides an assessment of the validity level of the LKPDbasedpon the scientificoapproach developed by the researcher. Basedpon theiresults ofithevalidators, validation results obtained based on the assessment of two validation expertsand one material expert with an average score of 3.45% and 3.43% with the Very Validcategory as LKPD on global warming material. Thus , the developed LKPD has met theeligibility criteria.